Characteristics of cogen ash and the effect of its application on soil properties under paddy cultivation - HAMSA, N.; SRINIVASAMURTHY, C. A.; BHASKAR, S. (Journal of Soil and Water Conservation, 2020)
Cogen Ash, a by-product of sugar mills obtained during co-generation process to generate heat and electrical energy by burning bagasse and/or coal was used to study its effect on soil properties, growth and yield of paddy. Experiment was conducted in two plots at research block of Sri Chamundeshwari Sugars Ltd., K.M. Doddi, Mandya during kharif 2014 with 13 treatments replicated thrice using randomized complete block design. The cogen ash used was more of 0.002 to 0.02 mm size. Maximum water holding capacity was 61.1%, alkaline in nature with medium electrical conductivity and traces of total nitrogen and carbon content. Total phosphorus, potassium, sodium, calcium, magnesium and sulphur contents were 0.82, 1.193, 0.09, 0.79, 0.31, 0.014%, respectively. The pH and electrical conductivity of soil after the harvest of paddy crop did not vary significantly due to cogen ash application. Addition of cogen ash affects the soil nutrient status, this is due to the changes in soil pH that affects nutrient solubility and due to soil enrichment by soluble salts and nutrient elements present in the ash. Hence, cogen ash can be safely used in agriculture.